2003
DOI: 10.1002/mc.10145
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A, an inhibitor of histone deacetylases, strongly suppresses growth of pancreatic adenocarcinoma cells

Abstract: In cells with an altered p53 gene, the expression of p21(WAF1/CIP1), a potent inhibitor of cyclin-dependent kinases, can be induced by histone deacetylase (HDAC) inhibitors via a p53-independent pathway, which may play a critical role in arrest of cell growth. Accordingly, HDAC inhibitors such as trichostatin A (TSA) have potential utility in pancreatic cancer, as most of these tumors possess mutations in p53, which in fact is the main cause of chemoresistance to 5-fluorouracil. We have analyzed the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 37 publications
5
75
2
Order By: Relevance
“…Recently, Donadelli et al have described the effect of TSA on nine pancreatic adenocarcinoma cell lines (49). Interestingly, the nine cell lines used in that study were different from the ones used in this report, which makes our results even stronger because we can conclude that at least 12 different pancreatic adenocarcinoma cell lines undergo apoptosis after TSA and other histone deacetylase inhibitors treatment.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Recently, Donadelli et al have described the effect of TSA on nine pancreatic adenocarcinoma cell lines (49). Interestingly, the nine cell lines used in that study were different from the ones used in this report, which makes our results even stronger because we can conclude that at least 12 different pancreatic adenocarcinoma cell lines undergo apoptosis after TSA and other histone deacetylase inhibitors treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…Whereas specific caspase inhibitors are unable to block TSA-induced apoptosis in our cell lines, serine protease inhibitors completely block this apoptosis induction. No data using specific caspase inhibitors were used by Donadelli et al (49). We used again the PANC-1 cell line to determine the caspase-3 activity evoked by TSA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of histone deacetylases (HDACs) have also been demonstrated to induce cell growth arrest and apoptosis in a variety of tumor cells [14][15][16][17][18]. One of the HDACs inhibitors SAHA is currently in clinical trials for patients with hematological or solid tumors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, tumor cells may acquire more rapid growth activity and more malignant potential as p21 WAF1 expression decreases. It was repor ted that two histone deacetylation inhibitors, trichostatin A and sodium butyrate, cause accumulation of acetylated histone H3 and H4 [14] . This action most likely occurs in vivo because in rats fed with a high-fiber diet, high butyrate levels are correlated with histone hyperacetylation in colonic epithelial cells [15] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the potential correlation between tumor-related genes and biological behaviors remains controversial. For example, one recent report [17] demonstrated that allelic deletion on chromosome 18q is associated with poor survival of patients with stage Ⅱ colorectal cancer, while another study [18] showed that this phenomenon does not provide any prognostic information, suggesting that construction of composite genetic profiles of tumor tissue, with inclusion of several tumor markers, may be premature [14] . It is necessary to further investigate how histone modifications impact the neoplastic process, and to study the means for prevention and treatment of colorectal carcinoma, such as chromatin structure alteration and activation of specific tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%